Sown wildflower fields and hedgerows synergistically promote insectivorous bats - Franziska Peter; Rebecca Bleumer; Christina Martinez Christophersen; Sally Matern; Tim Diekötter (Conservation Science and Practice)
Abstract Despite their relevance for anthropogenic impacts on biodiversity, synergistic effects are rarely considered in conservation science or management. However, the implementation of single agri‐environment measures may limit their potential benefits for biodiversity since species often require a multitude of complementary key resources, particularly in homogeneous and structurally poor landscapes. To advance conservation management, we studied whether hedgerows promote benefits of sown wildflower fields for insectivorous bats in temperate agro‐ecosystems. At 12 study sites, we simultaneously monitored bat activity and insect abundances from early to late summer at paired locations, that is, the ecotone of a sown wildflower field bordering a hedgerow and an open boundary of the same wildflower field. Particularly in early and mid‐summer, we found distinct preferences of bats for the ecotone of wildflower field and hedgerow. Yet, independent of the season, neither insects nor specifically moths showed a significant preference for the ecotone. Finally, both bat activity as well as insect abundances shifted towards the ecotone when distance to the nearest forest patch was high. We showed that synergies of hedgerows and wildflower fields promote benefits of the latter for both edge‐ and open‐space foraging bats, particularly in homogeneous and structurally poor agricultural landscapes. Therefore, successful conservation management should take advantage of synergies between complementary conservation measures at the local patch scale and at the same time, account for landscape composition and configuration.